Distribution and conservation of the African manatee (Trichechus senegalensis, Link 1795) in the Petit Loango and Setté Cama Ramsar sites (Gabon) - (:unkn) unknown (My University, 2022)
Gabon, a humid and forested equatorial country, has designated 2.8 million ha aswetlands of international importance under the Ramsar Convention. Petit Loango and SettéCama are its sites of rich biodiversity and prime habitat for the African manatee (Trichechussenegalensis). The lack of information on the current distribution of manatees in Gabon hindersconservation approaches for this aquatic mammal. It is through a bibliographic review, that thehistorical distribution was established. Then, from a field survey, data were collected on thepresence/absence of the manatee in the Ramsar sites of Petit Loango and Setté Cama. Thus,observations along sampling transects in the lagoons Iguéla, Ndougou, lakes Sounga, Cachimbaand the rivers Rembo Ngové Rembo Eshira, Rembo Ndougou have allowed systematic surveysof the direct presence of manatees, between 2016 and 2020. The results gave, through directobservation, the distribution and ecological preferences of manatees, thus defining the naturallimits of their populations in the Ramsar sites of Petit Loango and Setté Cama, and thenestablishing the conservation status of the species.
Keywords: African Research